PHYTOESTEROGEN COMPONENT OF ETHANOLIC ROOT EXTRACT OF FLAXSEED (Boehmeria nivea) DECREASES CHOLESTEROL SERUM LEVEL ON OVARIECTOMIZED RATS) - Ika Rahmawati Sutejo (Program Studi Ilmu Keperawatan Universitas Jember, 2016)
Dyslipidemia is a major cause of morbidity, mortality and high cost of treatment. Dyslipidemia associated with coronary heart disease (CHD), which causes 4 million deaths every year. Estrogen, a hormone produced by women during menarche protect